Are cocoa plantations suitable habitats? Network between parasites (Diptera: Hippoboscidea) and hosts (Mammalia: Chiroptera) in cocoa-dominated landscapes of the Brazilian Amazon - Dias, Samantha Valente; Alexandre, Rafaela Jemely Rodrigues; Correia, Letícia Lima; Aguiar, Ludmilla M. S.; Graciolli, Gustavo; Alcantara, Daniel Maximo Correa; Vieira, Thiago Bernardi (Frontiers in Ecology and Evolution, 2025)
IntroductionThe relationship between ectoparasitic flies and bats is influenced by anthropogenic changes in natural environments. In the Amazon, various forms of disturbance contribute to ecosystem imbalance, potentially leading to the local extinction and disruption of ecological functions. Cacao cultivation has been expanding in the Amazon, but studies on its impacts on bat diversity are still limited, hindering the development of effective conservation strategies. This study aims to assess bat and batfly species to understand how land-use changes affect antagonistic interaction networks between ectoparasitic flies and Phyllostomidae bats. MethodsWe sampled urban areas, natural vegetation, and cacao plantations using 10 mist nets over 69 nights at 36 sites across 10 municipalities in Pará.ResultsThe overall interaction network showed 42 host species and 52 ectoparasite species, showing high specialization, low connectivity, and insignificant nesting and parasite vulnerability. The highest ectoparasites richness was observed in natural vegetation (47), followed by cacao (30) and urban areas (29). The cacao-dominated network exhibited high modularity, natural areas had the highest occurrence of infracommunities, followed by urban areas and cocoa. Five bat species were present in all three environments, each infested with infracommunities. Notably, infracommunal associations were common among ectoparasite genera Speiseria, Strebla, and Trichobius.DiscussionThe species richness observed highlights Pará as a region of exceptional diversity for dipteran ectoparasites of bats (with 60 species). Our study suggests that cacao plantations can serve as suitable habitats for both bats and flies. Notably, we conducted this research on a small, family-run farm. While these types of farms are not substitutes for natural vegetation, they may help mitigate the impacts of rapid land-use and land-cover change. In fact, these small, family-operated farms demonstrated habitat suitability close to that of natural vegetation areas, supporting greater biodiversity within agricultural landscapes.